High risk pregnancy and Fetal outcome at Shree Birendra Hospital - Singh, Arju Chaud; Khatri, Ratna; Rana, Sadikchya Singh; Malla, Rosy; Thapa, Sumana; Acharya, Indira (Journal of Society of Surgeons of Nepal, 2017)
Introduction: High risk pregnancy is a major cause of morbidity and mortality in a developing country. These patients are recognized in the initial prenatal office visit as they have a poor obstetrical history or a well recognized medical complication however; pregnancy becomes high risk because they develop unexpected complications in the course of otherwise normal pregnancies. The objective of this study is to identify various type of high risk pregnancy and fetal outcome. Methods: This was a descriptive study conducted in Shree Birendra military hospital over a period of 9 months. Patients were recognized as high risk during antenatal visit and during admission. They were followed till delivery. The case records of all high risk pregnancy with their fetal outcome were analyzed. Statistical analysis was done using simple percentage. Results: Total deliveries during study period was 626. High risk pregnancy identified were 99 (15.81%). Previous lower segment cesarean section was the most common identified high risk pregnancy 34 (5.43%) followed by young primigravida 3.19%, breech 2.23%. There were total 13 low birth weight baby (13.13%) and 2 stillbirth (2%) as fetal outcome. Conclusion: Identification of high risk pregnancy during antenatal period will reduce adverse perinatal outcome.